Rough sleepers eaudiobook Dr. jim o'connell's urgent mission to bring healing to homeless people. - Kidder, Tracy (Books on Tape, 2023)
NEW YORK TIMES BESTSELLER • The powerful story of an inspiring doctor who made a difference, by helping to create a program to care for Boston’s homeless community—by the Pulitzer Prize–winning, New York Times bestselling author of Mountains Beyond Mountains “I couldn’t put Rough Sleepers down. I am left in awe of the human spirit and inspired to do better.”—Abraham Verghese, author of Cutting for Stone   A BEST BOOK OF THE YEAR: NPR, BookPage, Chicago Public Library Tracy Kidder has been described by The Baltimore Sun as “a master of the nonfiction narrative.” In Rough Sleepers, Kidder tells the story of Dr. Jim O’Connell, a gifted man who invented a community of care for a city’s unhoused population, including those who sleep on the streets—the “rough sleepers.” After Jim O’Connell graduated from Harvard Medical School and was nearing the end of his residency at Massachusetts General, the hospital’s chief of medicine made a proposal: Would he defer a prestigious fellowship and spend a year helping to create an organization to bring health care to homeless citizens? That year turned into O’Connell’s life’s calling. Tracy Kidder spent five years following Dr. O’Connell and his colleagues as they work with thousands of homeless patients, some of whom we meet in this illuminating book. We travel with O’Connell as he navigates the city streets at night, offering medical care, socks, soup, empathy, humor, and friendship to some of the city’s most endangered citizens. He emphasizes a style of medicine in which patients come first, joined with their providers in what he calls “a system of friends.” Much as he did with Paul Farmer in Mountains Beyond Mountains , Kidder explores how Jim O’Connell and a dedicated group of people have improved countless lives by facing and addressing one of American society’s most difficult problems, instead of looking away.